Pemberdayaan Remaja Putri dalam Penanganan Nyeri Menstruasi Melalui Pelatihan Akupresure - Maharani Setianingsih; Heni Hirawati Pranoto; Wahyu Nur Mahayati (Universitas Ngudi Waluyo, 2022)
From the World Health Organization (WHO) showed on incidence of 1.769.425 (90%) women who experienced dysmenrohea. The prevalence of primary dysmenrohea in Indonesia is quite high 60 – 75% in young women. The prevalence of primary dysmenrohea in Indonesia is 64.25% consisting of 54.89% primary dysmenrohea and 9.36% secondary dysmenrohea (Aya. 2019). Dysmenrohea is not a disease but a symptom that arises due to abnormalities in the pelvic cavity and interveres wth womens activities. Management of dysmenorhea can be handled by giving pharmacological and non pharmacological therapy. In pharmacological therapy non steroidal anti inflamatory drugs can be given. Non pharmacologically that can be done with accupressure techniques (Indrayani,T & Antiza, V. 2021). improving adolences knowledge and skills abaout accupressure to treat menstrual pain. In the implementation of this community midwifery practice, is carried out in 3 stage, that is direct interviews, literature study, active participation. The results obtained 3 adolescent girls (100%) understand about dysmenorhea. Pos test data obteined after being given on simulation on accupressure to reduce menstrual pain found 2 adolescent (75%) understood acupressure and 1 adolescent girl (25%) still did not understand accupressure to reduce menstrual pain. Young women already know how to deal with menstrual pain with non-pharmacological therapy in the form of acupressure massage AbstrakData dari World Health Organization (WHO) didapatkan kejadian sebesar 1.769.425 jiwa (90%) wanita yang mengalami dismenore. Prevalensi dismenore primer di Indonesia cukup tinggi yaitu 60-75% pada perempuan muda. Prevalensi dismenore di Indonesia 64,25% yang terdiri dari 54,89% dismenore primer dan 9,36% dismenore sekunder (Aya. 2019). Dismenore bukanlah suatu penyakit, melainkan gejala yang timbul akibat adanya kelainan dalam rongga panggul dan mengganggu aktivitas perempuan. penangganan dismenore dapat ditangani dengan pemberian terapi farmakologi dan non farmakologi. Pada terapi farmakologi dapat diberikan obat-obatan anti inflamasi non-steroid. Secara nonfarmakologi yang dapat dilakukan dengan teknik akupresur (Indrayani,T & Antiza, V. 2021). Meningkatkan pengetahuan dan keterampilan remaja tentang akupresure untuk mengatasi nyeri menstruasi Dalam kegiatan pengabdian masyarakat dilakukkan dalam beberapa tahap, yaitu: wawancara langsung,study literature, partisipasi aktif. Hasil yang diperoleh, yaitu 3 remaja (100%) memahami tentang dismenorea. Data post test yang didapatkan setelah dberikan simulasi mengenai akupresur mengurangi nyeri menstruasi didapatkan 2 remaja (75%) memahami pemijatan akupresure dan 1 remaja (25%) masih kurang memahami pemijatan akupressure untuk mengurangi nyeri menstruasi. Remaja putri sudah mengetahui cara untuk mengatasi nyeri menstruasi dengan terapi non farmakologi berupa pijat akupresur.